Determinan Partisipasi Inspeksi Visual Asam Asetat pada Pengguna Kontrasepsi Oral di Wilayah Kerja Puskesmas Mangli - Alifianisa Maya Indra Cahyani (Fakultas Kesehatan Masyarakat, 2026)
Cervical cancer is the 4th leading cause of cancer-related mortality among women worldwide. Global burden of cervical cancer is projected to increase markedly by 2050. The disease can be prevented through early detection screening. In Indonesia, Visual Inspection with Acetic Acid (VIA), an effective and affordable screening method, remains considerably participant below the national target. Oral contraceptive users constitute a priority population for cervical cancer prevention because prolonged hormonal contraceptive use has been associated with an increased risk of cervical cancer. This study aimed to analyze the association between individual beliefs based on the Health Belief Model and participation in VIA screening among oral contraceptive users at Mangli Public Health Center, Jember Regency. This study employed quantitative analytical descriptive design with a cross–sectional studies. The study was conducted in the working area of Mangli Primary Health Center, Jember Regency, involving 113 oral contraceptive users selected through simple random sampling. Data were collected using the Health Belief Model modification questionnaire from Damtie et al. (2023); Guvenc et al. (2010); and Ghalavandi et al. (2021). Data analysis was performed using the chi-square test, with p-values < 0.05 and Confidence Interval 95%. Results showed that most respondents had never undergone VIA screening (63.7%). The bivariate analysis demonstrated that perceived severity, perceived benefits, perceived barriers, and self-efficacy were significantly associated with participation in VIA screening. These variables increased the likelihood of participating in VIA screening by approximately 2.7 to 3.8 times compared with respondents who reported lower levels of these Health Belief Model constructs. VIA screening participation among oral contraceptive users was primarily determined by women's perceptions of disease severity, screening benefits, perceived barriers, and confidence in their ability to undergo screening. These findings highlight the importance of incorporating HBM-based behavioral strategu into cervical cancer prevention programs to strengthen positive health beliefs, reduce perceived barriers, enhance self-efficacy, and ultimately improve VIA screening uptake among women at increased risk.
Validasi dan Finalisasi Ratna 6 Agustus 2026
Keywords: Kanker serviks; Inspeksi Visual Asam Asetat; Kontrasepsi oral; Health Belief Model